Neural correlates of human fear conditioning and sources of variability in 2199 individuals - Joaquim Radua; Hannah S. Savage; Enric Vilajosana; Alec Jamieson; Birgit Abler; Fredrik Åhs; Tom Beckers; Narcís Cardoner; Josh M. Cisler; Juliana B. Diniz; Dominik R. Bach; Sigrid Elsenbruch; et al. (Nature Communications)
Abstract Pavlovian fear conditioning is a fundamental process in both health and disease. We investigate its neural correlates and sources of variability using harmonized functional magnetic resonance imaging data from 2199 individuals across nine countries, including 1888 healthy individuals and 311 with anxiety-related or depressive disorders. Using mega-analysis and normative modeling, we show that fear conditioning consistently engages brain regions within the “central autonomic–interoceptive” or “salience” network. Several task variables strongly modulate activity in these regions, contributing to variability in neural responses. Additionally, brain activation patterns differ between healthy individuals and those with anxiety-related or depressive disorders, with distinct profiles characterizing specific disorders such as post-traumatic stress disorder and obsessive-compulsive disorder. While the neural correlates of fear conditioning are highly generalizable at the population level, variability arises from differences in task design and clinical status, highlighting the importance of methodological diversity in capturing fear learning mechanisms.